(untitled) (Research, Society and Development, 2021)
Introduction: Health professionals attend to all types of emergencies and patients, such as those affected by COVID-19, facing critical and stressful situations that can favor the development of compassion fatigue (CF). Objective: To characterize the scientific production and synthesize the most relevant aspects of CF in health professionals during the COVID-19 pandemic. Methods: Integrative literature review in the databases BVS, MEDLINE via PubMed, PsycINFO, CINAHL, Web of Science and Scopus. For the search strategy, the following descriptors were used: “compassion fatigue”, “health personnel” and “coronavirus infections”. The inclusion criteria were original articles published from March 2020 to February 2021, available electronically in their entirety, without language restrictions, and that assessed CF in health professionals during the COVID-19 pandemic. Results: Thirteen articles were eligible and, from the analysis of these, two categories emerged: presence of CF and factors related to CF. Conclusion: Health professionals presented CF, predominantly in women, physicians, nurses and those working in specific care units for patients with COVID-19. Among the factors related to CF were mental health, ethical, occupational and sociodemographic issues. The findings indicate the need for assessment, monitoring and treatment of this condition in health professionals during the pandemic.